2006
DOI: 10.1093/comjnl/bxl019
|View full text |Cite
|
Sign up to set email alerts
|

Computation of Elementary Siphons in Petri Nets For Deadlock Control

Abstract: When designing liveness-enforcing Petri net supervisors, unlike other techniques, Li et al. added control places and arcs to a plant net model for its elementary siphons only, greatly reducing the structural complexity of the controlled system. Their method, however, suffers from the expensive computation of siphons. We propose a new T-characteristic vector z to compute strict minimal siphons (SMS) for S 3 PR (systems of simple sequential processes with resources) in an algebraic fashion. For a special subclas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 26 publications
(45 reference statements)
0
101
0
Order By: Relevance
“…based on the theory in [15] in the partial controlled model in Fig. 3) cannot be emptied based on the theory in [17].…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…based on the theory in [15] in the partial controlled model in Fig. 3) cannot be emptied based on the theory in [17].…”
Section: Theorymentioning
confidence: 99%
“…Consequently, deadlocks occur due to processes holding resources mutually waiting for others to release their resources. Deadlock prevention [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] adds monitors to problematic siphons to prevent them from becoming insufficiently marked.…”
mentioning
confidence: 99%
“…One would get away with such troubles for a simple basic subclass of S 3 PR (called BS 3 PR in [13]), where the set of elementary and dependent siphons correspond to that synthesised from elementary and compound (i.e. multiple interconnected) resource circuits (containing only resource places), respectively.…”
Section: Elementary Siphons and Characteristic Vectorsmentioning
confidence: 99%
“…In [16], a polynomial time algorithm was proposed to find elementary siphons in a graphical fashion, where we also showed that an SMS can be synthesised from a strongly resource subnet in an S 3 PR. The author further proved in [13] that each elementary siphon can be synthesised from an elementary resource circuit, whereas a dependent siphon can be synthesised from a compound resource circuit…”
Section: Graphical Search Of Elementary Siphonsmentioning
confidence: 99%
“…Monitors or control places and related arcs are often used to achieve such purposes Ezpeleta et al [1995], , Li and Zhou [2004], Huang et al [2001], Chao [2006], , and Uzam [2004]. The work of Ezpeleta et al [1995] is usually considered to be the first using structure theory of Petri nets to design monitor-based liveness-enforcing Petri net supervisors for FMS.…”
Section: Introductionmentioning
confidence: 99%